Aegean mercenaries in light of the Bible : clash of cultures in the story of David and Goliath - Rodan, Simona, (Archaeopress Publishing Ltd, 2015)
The story of the duel of David and Goliath, the Philistine champion, is narrated in the Bible in several versions. While its symbolic importance in Judaism and later in Christianity gradually came to represent the battle between good and evil, true faith and paganism, attempts were made since ancient times to solve its ambiguities. In modern research, the story arouses many disputes. There is controversy about the degree of realism and fantasy in it and there is also no agreement as to the time it was composed. The purpose of this study is not only to shed light on the enigmas about the protagonists and the time of the story, but also to understand why the importance of its message did not lessen and in what circumstances the interest in it was prolonged.